On Location Theory and Practice in Classroom-Based Writing Tutoring - Spigelman, Candace; Grobman, Laurie (University Press of Colorado, 2005)
Classroom-based writing tutoring is a distinct form of writing support, a hybrid instructional method that engages multiple voices and texts within the college classroom. Tutors work on location in the thick of writing instruction and writing activity. On Location is the first volume to discuss this emerging practice in a methodical way. The essays in this collection integrate theory and practice to highlight the alliances and connections on-location tutoring offers while suggesting strategies for resolving its conflicts. Contributors examine classroom-based tutoring programs located in composition courses as well as in writing intensive courses across the disciplines.